Subjetividade transexual: A visibilidade do sujeito nos jogos de verdade - Leite, Isadora Damasceno Ribeiro de Oliveira (2017)
This work aims to understand about the trans subjectivity, through the experience reports of people considered - socially and politically - transsexuals. The question "what does trans?" emerges as a central problematic intending to think about subjectivity aspects of the trans subject and the discourse of truth about itself. Through queer studies - mainly the deconstructive hypothesis of identity and gender notions from the philosopher Judith Butler -, it is intended to think about the conditions of visibility given to the trans subject, since scientific [medical/legal] knowledge/power through normative significance of the sexed body and the consequent configuration of gender identity notions, makes it an abject, marginal, intolerable, and therefore socially invisible subject. Once invisible and conditioned to isolation, the trans subject - in its subjectivity - points to the impossibility of creating itself - dehumanized - in the midst of the plurality of identity projects.